Individual- and Environmental-Level Predictors of Recess Activity and Sedentary Behavior: Findings from the I-CAN! Study. Issue 4 (22nd September 2022) - Bartholomew, John B.; Clutton, Jon; Burford, Katie; Aadland, Eivind; Resaland, Geir Kare; Jowers, Esbelle M.; Errisuiz, Vanessa
ABSTRACT: Introduction/Purpose: Recess represents a prime opportunity for physical activity during the school day. However, evidence is mixed with regard to factors associated with activity during recess. Methods: Data were collected as a part of the Texas Initiative for Children's Activity and Nutrition (I-CAN!) program from 14 elementary schools and 1049 fourth-grade students. Percent of time in moderate-to-vigorous physical activity (MVPA) and sedentary behavior during recess was measured using GT3X+ accelerometers. Students' demographics, aerobic fitness, and body mass index were collected from school records and FITNESSGRAM® data. Aspects of the playground environment supporting activity (e.g., soccer goals) or sedentary behavior (e.g., benches) were calculated following the procedures of the System for Observing Play and Leisure Activity in Youth, with recess spatial area calculated via the polygon measurement tool in Google™ Earth Pro software. Recess time was collected from school data. Weather during recess was determined using time-stamped archived weather data from Weather Underground. Two-level, linear mixed model regression examined associations between individual- and school-level characteristics and percent time in MVPA. Results: At the student level, boys were more active than girls (effect size (ES) = 0.50), and percent time in MVPA was directly associated with aerobic fitness (ES = 0.35). At the school level, recess infrastructure was associated with percent time in MVPA (ES = 1.45), except for factors related to sedentary behavior, which were indirectly associated with percent time in MVPA (ES = −1.98). Patterns for sedentary behavior mirrored these effects. Conclusions: This is one of the few studies to test the associations of fitness and sedentary upgrades to play areas with MVPA and sedentary behavior. The results suggest that recess is most likely to support MVPA in boys and those who are already most fit (i.e., those who would not be the target of intervention). This is not surprising because the focus of recess is on free choice of play, and thus recess might be supported more for social and emotional benefits than the effect on physical activity.